2020
DOI: 10.1002/jpen.1934
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Refeeding Syndrome and Clinical Outcome in Extremely Low‐Birth‐Weight Babies: Secondary Cohort Analysis From the ProVIDe Trial

Abstract: Background Refeeding syndrome (RS) following preterm birth has been linked to high intravenous (IV) protein intake in the presence of low electrolyte supply. In extremely low‐birth‐weight (ELBW) babies, we aimed to determine the incidence of RS and associations with birth characteristics and clinical outcomes. Method Prospective cohort study of ELBW ProVIDe Trial participants in 6 New Zealand neonatal intensive care units. RS was defined as serum phosphate < 1.4 mmol.L−1 and total calcium > 2.8 mmol.L−1. Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 55 publications
2
51
2
Order By: Relevance
“…There were only 4 patients with neonatal refeeding syndrome with hypercalcemia and hypophosphatemia at 1 week of life, and 3 of them resolved after second week of life. The result is comparable to most of the clinical studies in which neonatal refeeding syndrome occurs during the first week of life and no cases are reported after 2 weeks of life until now 23,27,29–33 . The major cause of hypophosphatemia in ELBW infant at 2 weeks of life is inadequate mineral supplement, and it could be in infant with either persistent hypophosphatemia after neonatal refeeding syndrome, or gradually lowering serum P level from normal mineral status at 1 week of life.…”
Section: Discussionsupporting
confidence: 81%
“…There were only 4 patients with neonatal refeeding syndrome with hypercalcemia and hypophosphatemia at 1 week of life, and 3 of them resolved after second week of life. The result is comparable to most of the clinical studies in which neonatal refeeding syndrome occurs during the first week of life and no cases are reported after 2 weeks of life until now 23,27,29–33 . The major cause of hypophosphatemia in ELBW infant at 2 weeks of life is inadequate mineral supplement, and it could be in infant with either persistent hypophosphatemia after neonatal refeeding syndrome, or gradually lowering serum P level from normal mineral status at 1 week of life.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, studies of higher intakes of macronutrients in very preterm babies in the early postnatal period are associated with other metabolic derangements, including the refeeding syndrome. 27 The refeeding syndrome was found to be associated with a higher rate of sepsis in a study of enhanced compared with standard feeding. 28 The preterm brain is especially susceptible to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of higher intakes of macronutrients in very preterm babies in the early postnatal period are associated with other metabolic derangements, including the refeeding syndrome. 27 The refeeding syndrome was found to be…”
Section: Original Researchmentioning
confidence: 99%
“…Of note, this study was discontinued early due to a high occurrence of a refeeding like syndrome among the intervention infants [11]. The risk of refeeding like syndrome has been confirmed by others [12][13][14][15] and the early need for phosphate and potassium supplementation is highlighted in the revised European guidelines on Pediatric Parenteral Nutrition [16,17]. Moreover, this underlines the importance of conducting well-designed trials on nutritional management in this patient population.…”
Section: Introductionmentioning
confidence: 71%
“…We have used data from the PRENU-cohort for our determination of sample size. The PRENU study showed decreased regional white matter mean diffusivity (MD), suggestive of improved maturation of cerebral connective tracts in the intervention group [15]. The MD in the superior longitudinal fasciculi was 1.18 × 10-3 (6.18 × 10-2) in the intervention group and 1.25 × 10-3 (5.70 × 10-2) in the control group.…”
Section: Sample Sizementioning
confidence: 99%